2016
DOI: 10.15252/embr.201642540
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Nat4 and its associated histone H4 N‐terminal acetylation mediates calorie restriction‐induced longevity

Abstract: Changes in histone modifications are an attractive model through which environmental signals, such as diet, could be integrated in the cell for regulating its lifespan. However, evidence linking dietary interventions with specific alterations in histone modifications that subsequently affect lifespan remains elusive. We show here that deletion of histone N‐alpha‐terminal acetyltransferase Nat4 and loss of its associated H4 N‐terminal acetylation (N‐acH4) extend yeast replicative lifespan. Notably, nat4Δ‐induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 108 publications
1
42
0
Order By: Relevance
“…Downregulation of NatA resulted in plant adaptation and, therefore, drought resistance. A perhaps similar recent finding is that, in yeast, calorie restriction downregulates NatD and reduces the Nt acetylation of a specific substrate, leading to increased stress resistance and longevity, described further below (Molina-Serrano et al, 2016). Another example is that NAA10, the catalytic subunit of NatA, is hydroxylated during normoxia, changing its enzymatic properties (Kang et al, 2018), as discussed below.…”
Section: Regulation Of Nt Acetylationmentioning
confidence: 60%
“…Downregulation of NatA resulted in plant adaptation and, therefore, drought resistance. A perhaps similar recent finding is that, in yeast, calorie restriction downregulates NatD and reduces the Nt acetylation of a specific substrate, leading to increased stress resistance and longevity, described further below (Molina-Serrano et al, 2016). Another example is that NAA10, the catalytic subunit of NatA, is hydroxylated during normoxia, changing its enzymatic properties (Kang et al, 2018), as discussed below.…”
Section: Regulation Of Nt Acetylationmentioning
confidence: 60%
“…Previous studies have investigated the impact of H4K5 acetylation and N-terminal acetylation on H4R3 methylation. 20, 28, 29 However, there has yet to be a study that dissects the impact of the diverse H4K5 PTMs and H4 N-terminal acetylation on type I and type II PRMTs.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, by introducing the Nat4 gene under the control of a constitutive CR-insensitive promoter we, firstly, showed that CR was not able to reduce the levels of N-acH4, secondly, the induction of PNC1 and that of other stress-response genes was compromised and thirdly, the extension of replicative lifespan normally stimulated by glucose deprivation was limited in yeast cells. 3 Thus, our study proposes that N-acH4 mediated by Nat4 is an epigenetic barrier to longevity that can be removed by CR to promote its life-extending effects (Fig. 1).…”
mentioning
confidence: 79%
“…5 Consistent with this antagonistic relationship between N-acH4 and H4R3me2a, we found that absence of an arginine residue at position 3 in histone H4 (H4R3K) and abrogation of arginine methylation confers a significantly shorter cellular lifespan. 3 Altogether, these findings implicate a specific histone modification cross talk in a pathway that controls aging as a result of an external signal. In the future, it will be interesting to explore whether cross talks among other histone modifications occur in response to diet or other environmental stimuli to regulate lifespan (Fig.…”
mentioning
confidence: 89%
See 1 more Smart Citation